ISLAMIC EDUCATION AS A MEANS OF FOSTERING ECOLOGICAL AWARENESS: A REVIEW OF ENVIRONMENTAL ETHICS IN THE QUR’AN - Abdul Khalik; Muhammad Yusuf; Mardan Mardan; Hartina Hartina (Jurnal Konseling Pendidikan Islam, 2026)
Ecological awareness has become an urgent necessity amid increasing environmental degradation that directly affects human quality of life. In the Islamic perspective, environmental preservation is not merely a social practice but an integral part of the education of iman (faith), Islam (practice), and ihsan (excellence), which guide humans to fulfill their responsibility as stewards (khalifah) on Earth. This study aims to examine the theological and ethical foundations within Islamic teachings that position environmental responsibility as a fundamental dimension of religious life, as well as to formulate the conceptual relationship between these three pillars and ecological behavior. Using a library research method, this study collects and analyzes various literature sources, including the Qur’an, hadith, Islamic scholarly works, and relevant scientific studies. The findings reveal that iman serves as a spiritual force that nurtures human awareness of the importance of safeguarding Allah’s creation; Islam, through its legal and ethical system, provides practical guidance for maintaining cleanliness and environmental sustainability; while ihsan encourages individuals to act virtuously and sincerely toward the environment. Together, these values form a strong moral and religious foundation for building ecological awareness. This study concludes that environmental preservation is a comprehensive expression of religious devotion, and that Islamic education holds a strategic role in fostering environmental concern rooted not only in knowledge but also in spirituality and character. Integrating the values of iman, Islam, and ihsan within educational frameworks offers a conceptual solution for developing more holistic and sustainable ecological awareness.